The Impact of Full Day School Policy in Indonesia: A Juridical Analysis of Teacher Welfare and Children's Rights - Adzillah, Salsabila Nur Imatul; Dinana, Aqimi; Adzibah, Salsabila I'tilaful (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2024)
This research conducts a juridical analysis of the Full Day School (FDS) policy in Indonesia, focusing on its impact on teacher welfare and children's rights. The primary objective is to evaluate how the policy aligns with legal frameworks such as Law Number 14 of 2005 on Teachers and Lecturers and Law Number 35 of 2014 on Child Protection. This study utilizes an analysis of specific legal documents and policy regulations, including Ministerial Regulation Number 23 of 2017 on School Days and Presidential Regulation Number 87 of 2017 on Strengthening Character Education. The findings indicate that the policy’s extended school hours may infringe upon children’s rights to rest and play, as guaranteed under Law Number 35 of 2014, and exacerbate teacher workloads, potentially conflicting with labour rights under Law Number 13 of 2003. Teachers report heightened stress and reduced work-life balance, while students face mental fatigue and diminished extracurricular opportunities. To comply with legal mandates and international conventions such as the United Nations Convention on the Rights of the Child (UNCRC), the policy must be revised to balance instructional goals with the well-being of both educators and learners. Recommendations include reducing school hours, ensuring adequate rest periods, and aligning the policy with legal and international standards. Further exploration of the policy's long-term legal and social implications is essential for sustainable educational reform.